Structural and optical studies of condensed gases under extreme conditions - Wang, Mengnan (The University of Edinburgh, 2023)
Dense solidified gases are sources of rich physical and chemical phenomena and model objects to be widely used in theoretical calculations. The focus of this thesis has been the structural and optical properties of simple gases and gas mixtures under extreme conditions. Three simple dense gas systems, methane (CH₄), Xe-Ar mixture and nitrogen-trifluoride (NF₃) have been studied and characterized using high pressure and high temperature techniques in combination with Raman spectroscopy and x-ray diffraction in diamond anvil cells (DACs). CH₄ is one of the major constituents of the Uranus and Neptune interiors, and large amounts of it are also present in the deep Earth. As the simplest hydrocarbon, CH₄ presents a rich variety of crystal structures at low temperature and pressure regime. However, despite being widely studied, phase relations between numerous CH₄ phases are poorly understood even at relatively low pressure. In this thesis, by combining Raman spectroscopy and in-situ high-pressure, high-temperature resistive heating techniques, we demonstrate the complexity of the phase diagram of CH₄ up to 45 GPa and 1400 K. Changes in the frequencies and Raman profiles of the ν₁ and ν₃ vibrational modes of CH₄ molecule were used to detect phase transitions and construct boundaries between individual phases in the phase diagram. A triple point between fluid, phases I, and phase alone the melting curve was found and precisely located in the studied P-T range. The melting curve changes its slope above the triple point. Moreover, previously reported sluggish transitions from phase A to phase B was found to be controlled by kinetics. These results represent a significant revision of the existing phase diagram of CH₄. The second system under investigation is the binary mixture of xenon and argon. The simple closed-shell electronic configurations make rare gases and their mixtures an ideal system for comparing experiment with theory. Rare gases are archetypal van der Waals systems. Previously, no binary compound of Xe and Ar were known. We have explored rare gas solids Xe-Ar₂ system up to pressure of 60 GPa with combined Raman spectroscopy, x-ray diffraction and first-principles density functional theory (DFT) calculations. A novel van der Waals compound XeAr₂ has been observed at 3.5 GPa. We find that pressure stabilizes the formation of this stoichiometric, solid van der Waals compound of composition XeAr₂. Synchrotron x-ray diffraction shows that this compound adopts a MgZn₂-type crystal structure, which is in a Laves phase. Our DFT calculation of the formation enthalpy indicates that XeAr₂ stays stable to at least 80 GPa. The last condensed gas solid presented here is nitrogen-trifluoride (NF₃). Since first synthesized by molten salt electrolysis, NF₃ has attracted wide interests, ranging from fundamental study to industrial applications. However, structures and phase relations on NF₃ under high pressure remains unknown. In the contributing work, NF₃ has been studied by synchrotron x-ray diffraction and Raman spectroscopy combined with DFT calculation. At 300 K, NF₃ solidifies at 3.5 GPa into the orthorhombic structure (Pnma). Phase diagram of NF₃ has been studied by Raman spectroscopy, two solid phases have been observed between 77 and 300 K up to 120 GPa. Our DFT calculations suggests NF₃ remains stable to at least 150 GPa.
Keywords: diamond anvil cell; DAC; high pressure; x-ray diffraction; Raman spectroscopy; Xe-Ar; methane; nitrogen-trifluoride; high-temperature